Analisis Implementasi Algoritma Elias Delta Codes Untuk Kompresi File Audio - Noki Cahya Putra Pasaribu (Graha Mitra Edukasi, 2024)
The development of file sizes today is very diverse, some are small and large, one of the problems that is often encountered among the public is the large number of files stored in memory storage or hard disks on computers, Indeed, in this day and age, storage space already exists that can accommodate many files, but there are still those who do not have a large storage area, so that a lot of data is stored resulting in memory storage space and hard disks on the computer quickly full, and resulting in delays in the file delivery process, then the way that can be done is by compressing the file. One of the files sampled in this study is an audio file, then the solution to reducing the file size by compressing the file, by compressing the original size of the file will be different in size from the file that has been compressed, but it should be known that all compressed files also do not experience a reduction in size as well, when compressing requires a compression algorithm, in this study using the Elias delta codes algorithm, compressing using this algorithm, the original file with the file that has been compressed is different in size. The results of the research that has been done, in compressing audio files using the Elias delta codes algorithm has reduced the file size, proving that the compression technique carried out takes the hexadecimal value of the audio file as much as 22 reducing the file size 0.54% from the original mp3 file to 43.66 MB.